The Turkish Adaptation of the Green Motivation Scale and The Effect of the Green Organizational Climate on Green Motivation - Ali Erbaşı; Serap Kalfaoğlu (Istanbul Management Journal)
Today, where the concept of green gains increasing importance, why organizations want to exhibit green behaviors or what motivates them to act green is an important area of research. Looking at the subject at the individual level, examining employees’ perceptions about why organizations try to exhibit green behaviors and the effect of different variables on this perception will create different perspectives for the literature. The purpose of this study is to adapt the green motivation (GM) scale developed by Paulraj et al. (2017) to Turkey and to investigate the effect of a green organizational climate (GOC) on GM. For this purpose, data obtained from 375 employees of enterprises operating in different sectors in Konya with environmental policies were analyzed. A two-stage analysis was performed. In the first phase, a Turkish version of the GM scale was created and as a result, a valid and reliable scale consisting of 3 dimensions and 13 items was obtained in accordance with the original. In the second phase, hypothesis tests were conducted and it was understood that GOC had a statistically significant and positive effect on all dimensions of GM (instrumental motives, relational motives, moral motives). It is expected that the findings obtained from this research will provide a new perspective for individual, group, and organizational studies on GM in organizations.